PENGEMBANGAN MEDIA VIDEO MICROLEARNING UNTUK PEMBELAJARAN MANAJEMEN USAHA RITEL - Nor Khomala Sari, Silvi; Mariah, Siti; Kartikasari, Enggar (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2025)
The main issue in the learning process of the Retail Fashion Business Management course lies in the use of learning media, which currently consists of PowerPoint slides that only present key points, making them less engaging and failing to stimulate students' reading interest. This study aims to develop a more interactive and engaging microlearning-based video as a learning medium and to evaluate its feasibility. The research adopts a Research and Development (R&D) approach using the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. The resulting product is a series of microlearning videos accessible through the YouTube platform, intended to provide a more flexible and comprehensible learning experience. The feasibility of the media was assessed by two subject matter experts and two media experts using a questionnaire instrument. Validation results indicate that the developed learning media is highly feasible, with a feasibility score of 92.5% from subject matter experts and 85.93% from media experts. The conclusion of this study is that microlearning-based video media is effective for use in the Retail Fashion Business Management course. The scientific contribution of this research lies in offering an alternative digital learning model that aligns with the characteristics of digital-native learners and enriching the repertoire of interactive media in vocational education, particularly in the development of managerial competencies in the retail fashion sector.